2010
DOI: 10.1097/iae.0b013e3181cea676
|View full text |Cite
|
Sign up to set email alerts
|

Association Study of Complement Factor H, C2, Cfb, and C3 and Age-Related Macular Degeneration in a Han Chinese Population

Abstract: This study showed that SNPs rs3753394 (P = 0.0276), rs800292 (P = 0.0266), rs1061170 (P = 0.00514), and rs1329428 (P = 0.0089), but not rs7535263, rs1410996, or rs2274700, in CFH were significantly associated with wet AMD in a mainland Han Chinese population. This study showed that CFH was more likely to be AMD susceptibility gene at Chr.1q31 based on the finding that the CFHR1 and CFHR3 deletion was not polymorphic in the cohort of this study, and none of the SNPs that were significantly associated with AMD i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
56
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 36 publications
5
56
0
7
Order By: Relevance
“…32,33 Genetic variants in the Complement Factor H (CFH) gene on chromosome 1q32 and two tightly linked genes-ARMS2 and HTRA1 on 10q26 have been identified as major contributors to nAMD development. [14][15][16]34 Our study identified that CFH rs800292 and rs2274700 showed significant difference between nAMD or PCV patients and controls, which was consistent with previous study in our laboratory. 35 We also identified that CFH rs1065489 was a risk factor in PCV, which had been proved in Japanese population.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…32,33 Genetic variants in the Complement Factor H (CFH) gene on chromosome 1q32 and two tightly linked genes-ARMS2 and HTRA1 on 10q26 have been identified as major contributors to nAMD development. [14][15][16]34 Our study identified that CFH rs800292 and rs2274700 showed significant difference between nAMD or PCV patients and controls, which was consistent with previous study in our laboratory. 35 We also identified that CFH rs1065489 was a risk factor in PCV, which had been proved in Japanese population.…”
Section: Discussionsupporting
confidence: 82%
“…CFH has been identified by various studies as a major AMD susceptible gene in the Chinese, Japanese, and Caucasian populations. [14][15][16][17] Previous studies have proved that multiple variants of CFH gene, such as I62V (rs800292), are associated with the risk of nAMD in different ethnic groups. [18][19][20][21] Beyond the complement pathway, the Age-Related Maculopathy Susceptibility 2 (ARMS2) locus at chromosome 10q26 has been implicated as another major genetic contributor to the nAMD disease process.…”
Section: Introductionmentioning
confidence: 99%
“…6 Many independent studies showed that the CFH gene has been identified as a causal polymorphism in western and Chinese populations. [6][7][8][9]23,24 Our results showed strong evidence that the genotypes and the haplotypes of two SNPs (rs800292 and rs1410996) of the CFH variant associate with AMD, and the joint effects might be strong for these two SNPs of CFH, but this finding must be replicated in future studies.…”
Section: Discussionmentioning
confidence: 74%
“…The association between SNPs in the C3 gene and AMD susceptibility has been established in multiple studies (Maller et al, 2007;Spencer et al, 2008;Park et al, 2009;Liu et al, 2010). Rs2230199 is a SNP in the C3 gene, which is a central component of all three pathways of complement activation -the alternative, classical, and mannose binding lectin pathways.…”
Section: Discussionmentioning
confidence: 99%